EFFECTIVENESS OF MISSOURI MATHEMATICS PROJECT (MMP) LEARNING APPROACH TO LEARNING TYPE OF TPS AND NHT TYPE ON ABILITY OF MATHEMATICS PROBLEM STUDENTS - Arif Masyari; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This study aims to determine is there a significant difference between the use MMP learning approach to TPS learning with the use MMP learning approach to NHT learning, and which is more effective between that lesson on math problem-solving ability. The population in this study were students of class XI MIPA MAN Yogyakarta III that consists of five classes. The sample in this study consists of two classes, that were XI MIPA 1 as the experimental class and XI MIPA 3 as the control class. The sampling technique used random sampling. The data collection method test and documentation. The research instrument is a problem solving test. Data analysis using t-test two parties and one party, but previously conducted test of normality and homogeneity. Based on the analysis of t-test two parties on mathematics problem-solving ability with a significance level of 5% and 55 degrees of freedom is obtained , indicating that there is a significant difference between the mathematics problem-solving ability using MMP learning approach to TPS learning with the use MMP learning approach to NHT learning, and Based on the analysis of t-test one parties with significance level of 5% and 55 degrees of freedom is obtained Â indicates that the MMP learning approach to TPS learning more effective than the MMP learning approach to NHT learning on mathematics problem-solving ability.